Trends and Applications of Brain Computer Interfaces - Yadav, Drishti; Yadav, Shilpee; Veer, Karan (Current Signal Transduction Therapy, 2021)
This article provides a comprehensive review of the recent trends and applications of BCIs. This review also provides future directions towards the acceleration and maturation of BCI technology. Based on a methodical search strategy, major technical databases were searched in quest of research papers of average and outstanding interest. A total of 188 research works were included within this review due to their suitability and state-of-the-art achievements. This review identifies various eminent applications of BCIs in medical and non-medical domains. The findings of this review reveal the need for further exploration of BCI devices outside the laboratory-based settings for their development and seamless integration. In addition, applications of BCIs, including neuromarketing, neurorehabilitation, and neuroergonomics, require additional investigations for further validation and fruition of BCI technology. Based on this review, it is concluded that BCIs are in their embryonic stage and seek further research and investigation for their maturation.
Keywords: EEG-based BCI